Building thermal resilience framework (BTRF): A novel framework to address the challenge of extreme thermal events, arising from climate change - Serdar, Mohammad Zaher; Macauley, Nadine; Al-Ghamdi, Sami G. (Frontiers in Built Environment, 2022)
Over the past two decades, the world has witnessed unprecedented record-breaking temperatures, and, in recent years, the rate of these extreme temperatures has increased, despite all climate change mitigation efforts. These extremes fall on both ends of the temperature spectrum and are a definite consequence of climate change. Examples of such extremes include the 2003 and 2022 heatwaves in Europe, claiming approximately 4000 and 12,000 lives, respectively as well as the 2021 heatwave in the Pacific Northwest region of North America and the deep freeze in Southeast Texas. In this paper, we reflect on previous studies, identifying both internal and external aspects that contribute to a building's thermal performance. We then incorporate these factors into a proposed framework, covering the important phases of a building's life cycle, to reflect its thermal resilience. During each phase, an associated Building Thermal Resilience Profile (BTRP), taken from accumulated data of previous phases, provides the needed assessment of the building, and is regularly adapted to changes in the building and its surroundings. BTRP will be a valuable tool for the resilience evaluation of different design options. Furthermore, during the operation phase, it will contribute to real-time monitoring and assessment, facilitating disaster management and response, at both the buildings and city scale, reducing the causalities of extreme events. Thus, the prime aim of this paper is to address the challenge of extreme thermal events, arising from climate change, and pave the way for the adoption of effective thermal resilience in building design and operation practices.